Utility of MRI for Evaluation of a Common Calcaneal Tendon Rupture in a Dog: Case Report - Lin, Megan; Glass, Eric N.; Kent, Marc (Frontiers in Veterinary Science, 2020)
An 8-year-old intact male German shorthaired pointer was presented for a left pelvic limb lameness. Examination revealed a plantigrade stance with flexed digits in the left pelvic limb, and swelling of the left common calcanean tendon distally. Magnetic resonance imaging revealed a partial rupture of the left common calcanean tendon, involving rupture to the tendons of the biceps femoris, gracilis, and semitendinosus muscles. Surgical repair was performed using a modified 3-loop pulley suture. Postoperatively, the tarsus was immobilized with external coaptation. Destabilization of the external coaptation occurred over 9 weeks followed by physical rehabilitation and complete return to function at 10 months postoperative. This case report illustrates the utility of MRI as a diagnostic tool for evaluation of tendon pathology. MRI provided exceptional detail of the tendons that comprise the common calcaneal tendon and the anatomical relationships to surrounding structures which facilitated appropriate surgical correction.